Sinergi Pemerintah Dan Lembaga Pendidikan Dalam Mencapai Tujuan Pendidikan (Studi Analisis Historis Madrasah Nizamiyyah) - Al Arifi, Nasiruddin (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2024)
Madrasah Nizamiyyah was the first Islamic educational institution that successfully initiated a modern classical education system in the Abbasid era. This success inspired new breakthroughs in the world of Islamic education in the future. This library research study uses a thematic approach with documentation data collection techniques in the form of collecting data from documents that correlate with research. The data was analyzed using the content analysis method and then verified using the source triangulation method. The research results show that the positive synergy between the government and educational institutions has become a mutualistic symbiosis which has a positive impact on both sides. Educational institutions benefit from government regulations that support the development of the education system and the fulfillment of basic needs, while the government benefits from the growing level of literacy and quality of community resources thereby improving the quality of the nation and state globally. Keyword: Synergy, Educational Goals, Education, Nizamiyyah